Fatigue as a long-term risk factor for limitations in instrumental activities of daily living and/or mobility performance in older adults after 10 years - Mueller-Schotte S (Dove Medical Press, 2016)
Sigrid Mueller-Schotte,1–3 Nienke Bleijenberg,1,2,4 Yvonne T van der Schouw,1 Marieke J Schuurmans2,4 1Julius Center for Health Sciences and Primary Care, University Medical Center Utrecht, the Netherlands; 2Department for the Chronically Ill, University of Applied Sciences Utrecht, the Netherlands; 3Department of Optometry and Orthoptics, University of Applied Sciences Utrecht, the Netherlands; 4Department of Rehabilitation, Nursing Science and Sports, University Medical Center Utrecht, the Netherlands Objectives: Decline in the performance of instrumental activities of daily living (IADL) and mobility may be preceded by symptoms the patient experiences, such as fatigue. The aim of this study is to investigate whether self-reported non-task-specific fatigue is a long-term risk factor for IADL-limitations and/or mobility performance in older adults after 10 years. Methods: A prospective study from two previously conducted cross-sectional studies with 10-year follow-up was conducted among 285 males and 249 females aged 40–79 years at baseline. Fatigue was measured by asking “Did you feel tired within the past 4 weeks?” (males) and “Do you feel tired?” (females). Self-reported IADLs were assessed at baseline and follow-up. Mobility was assessed by the 6-minute walk test. Gender-specific associations between fatigue and IADL-limitations and mobility were estimated by multivariable logistic and linear regression models. Results: A total of 18.6% of males and 28.1% of females were fatigued. After adjustment, the odds ratio for fatigued versus non-fatigued males affected by IADL-limitations was 3.3 (P=0.023). In females, the association was weaker and not statistically significant, with odds ratio being 1.7 (P=0.154). Fatigued males walked 39.1 m shorter distance than those non-fatigued (P=0.048). For fatigued females, the distance was 17.5 m shorter compared to those non-fatigued (P=0.479). Conclusion: Our data suggest that self-reported fatigue may be a long-term risk factor for IADL-limitations and mobility performance in middle-aged and elderly males but possibly not in females. Keywords: fatigue, instrumental activities of daily living, walking, aging